Quantitative Digitography Measures Fine Motor Disturbances in Chronically Treated HIV Similar to Parkinson’s Disease - Prabhakar, Varsha; Martin, Talora; Müller-Oehring, Eva M.; Goodcase, Ryan; Schulte, Tilman; Poston, Kathleen L.; Brontë-Stewart, Helen M. (Frontiers in Aging Neuroscience, 2020)
Abstract Introduction: Motor and cognitive deficits were compared in aging, chronically treated HIV people, people with mild-to-moderate stage Parkinson’s disease (PD) and healthy controls. Methods: Groups consisted of 36 people with PD, 28 with HIV infection and 28 healthy controls. Motor function was assessed with the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS-III) and a rapid alternating finger tapping (RAFT) task on an engineered keyboard known as Quantitative Digitography (QDG). Executive function, verbal memory and visuospatial processing were assessed using standard neuropsychological tests. Results: HIV demonstrated RAFT deficits similar to PD such as reduced amplitude (P=0.023) and greater amplitude variability (P=0.019) in the index finger when compared to controls. This fine motor disturbance correlated with HIV’s immune health, measured by their CD4+ T cell count (P<0.01). The UPDRS did not yield motor differences between HIV and controls. Executive function and verbal memory were impaired in HIV (P=0.006, P=0.016, respectively), but not in PD; visuospatial processing was similarly impaired in HIV and PD (P <0.05) although motor deficits predominated in PD. Conclusions: Fine motor bradykinesia measured quantitatively by QDG RAFT holds promise as a marker of motor decline related to current immune health in aging HIV patients and may be useful in longitudinal studies regarding mechanisms of immunosenescence versus potential toxicity of cART in this population. Additionally, motor and cognitive networks in HIV may be affected differently as the disease progresses as observed in the differential patterns of impairment between HIV and PD, providing insight into the mechanisms of brain deterioration in HIV.